2013
DOI: 10.1007/s00122-013-2231-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrating environmental covariates and crop modeling into the genomic selection framework to predict genotype by environment interactions

Abstract: Development of models to predict genotype by environment interactions, in unobserved environments, using environmental covariates, a crop model and genomic selection. Application to a large winter wheat dataset. Genotype by environment interaction (G*E) is one of the key issues when analyzing phenotypes. The use of environment data to model G*E has long been a subject of interest but is limited by the same problems as those addressed by genomic selection methods: a large number of correlated predictors each ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
312
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(332 citation statements)
references
References 12 publications
10
312
2
8
Order By: Relevance
“…Vermeulen et al (2013) illustrate how crop-climate modelling and analyses can pre-emptively inform the magnitude of adaptation required across a range of time scales. Process-based crop models have also been applied to direct future research and crop breeding (Heslot et al 2014;Falloon et al 2015;Challinor et al 2016). The benefits of different adaptation strategies have often been compared by their relative impact on yield (e.g.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…Vermeulen et al (2013) illustrate how crop-climate modelling and analyses can pre-emptively inform the magnitude of adaptation required across a range of time scales. Process-based crop models have also been applied to direct future research and crop breeding (Heslot et al 2014;Falloon et al 2015;Challinor et al 2016). The benefits of different adaptation strategies have often been compared by their relative impact on yield (e.g.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…The paper by Heslot et al (2014) is the only one we found where M 3 E effects also were modeled explicitly and where an effort was made to detect QTL with specific environmental variations. However, a Bayesian Lasso approach was used, which made it computationally impractical to model all marker 3 environment combinations together with the marker effects at once, and thus a multistep approach was needed, leading to quite a complex procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These early studies were mainly interested in mapping QTL that were stable across environments and thus obtained better estimates of the global genetic potential of an individual regardless of the environment. However, currently attention is directed more toward clarifying which QTL are susceptible to specific environmental covariables such as climatologic or soil conditions (Boer et al 2007;Heslot et al 2014). This makes it possible to define certain target populations of environments (TPEs) sharing some of the same environmental covariables so that environment-dependent QTL can be exploited for these TPEs (Heslot et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations